2018
DOI: 10.3389/fpsyg.2018.02452
|View full text |Cite
|
Sign up to set email alerts
|

The Shepard Illusion Is Reduced in Children With an Autism Spectrum Disorder Because of Perceptual Rather Than Attentional Mechanisms

Abstract: Earlier studies demonstrate reduced illusion strength in the Shepard illusion in adults and adolescents with an autism spectrum disorder (ASD) and in typically developing (TD) adults with high levels of autistic traits. We measured the strength of the Shepard illusion in ASD and TD children and tested if ten different eye-tracking measurements could predict group differences in illusion strength. The ASD children demonstrated reduced illusion strength relative to the TD group. Despite this, there were no mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Although seemingly contradictive of various sensorimotor research (e.g., Mosconi et al 2013; Buckingham et al 2016), this corresponds with a meaningful body of clinical evidence which has shown broad prediction-dependent capabilities to be typical in autistic people (Mostofsky et al 2004; Gidley-Larson et al 2008; Ego et al 2016; Tewolde et al 2018). Findings also align with recent evidence that autistic and neurotypical individuals attend to similar information when presented with visual illusions (Chouinard et al 2018). Consequently, in contrast to broad predictive accounts of autism (e.g., Pellicano and Burr 2012; Sinha et al 2014), our data indicate that links between sensorimotor prediction and autistic-like traits may not be due to any generic processing abnormalities, but rather due to context-sensitive ‘high-level’ mechanisms.…”
Section: Discussionsupporting
confidence: 90%
“…Although seemingly contradictive of various sensorimotor research (e.g., Mosconi et al 2013; Buckingham et al 2016), this corresponds with a meaningful body of clinical evidence which has shown broad prediction-dependent capabilities to be typical in autistic people (Mostofsky et al 2004; Gidley-Larson et al 2008; Ego et al 2016; Tewolde et al 2018). Findings also align with recent evidence that autistic and neurotypical individuals attend to similar information when presented with visual illusions (Chouinard et al 2018). Consequently, in contrast to broad predictive accounts of autism (e.g., Pellicano and Burr 2012; Sinha et al 2014), our data indicate that links between sensorimotor prediction and autistic-like traits may not be due to any generic processing abnormalities, but rather due to context-sensitive ‘high-level’ mechanisms.…”
Section: Discussionsupporting
confidence: 90%
“…Second, we know that the strength of the illusion increases as participants actively attend and scan the displaynamely the illusion strengthens with the number of saccades made between different elements in the display (Chouinard et al, 2018). This contrasts with other illusions, such as the verticalhorizontal illusion, that increase in strength as participants make less saccades and the image of the display is more stable on the retina (Chouinard et al, 2017).…”
Section: Mechanisms Underlying the Shepard Illusionmentioning
confidence: 94%
“…This method of normalising is used in many illusion studies (Chouinard et al, 2019;Chouinard et al, 2013;Chouinard et al, 2016;Chouinard et al, 2017;Chouinard et al, 2018;Schwarzkopf et al 2011;Sherman & Chouinard 2016) and allows for meaningful comparisons across studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations